Evaluation of pimobendan effect on sublingual microcirculation in an experimental pharmacology induced hypotension porcine model. (November 2022) - Magnin, Mathieu; Bonnet-Garin, Jeanne Marie; Laurenza, Chiara; Didier, Caroline; Gavet, Morgane; Nectoux, Alexandra; Allaouchiche, Bernard; Junot, Stéphane
Abstract: New therapeutic approaches are needed to simultaneously resuscitate macro- and microcirculation during circulatory shock. The aims of this study were to explore the microcirculatory and macrocirculatory effects of pimobendan, an inodilator with dual phosphodiesterase 3 inhibitor and calcium-sensitizing effects, in an experimental porcine model of pharmacologically induced hypotension associating vasoplegia and decreased cardiac output. Eight piglets were anesthetized and monitored for their hemodynamic parameters. Hypotension was induced by sevoflurane overdose until a mean arterial pressure between 40 and 45 mmHg was reached. A bolus of pimobendan (0.25 mg/kg) was administered intravenously thereafter. Sublingual microcirculation was evaluated using a Sidestream Dark Field imaging device. Hemodynamic and microcirculatory parameters were recorded at the baseline period (A), immediately before pimobendan administration (B) and after pimobendan administration (C). Induction of hypotension was associated with a decreased cardiac index and microcirculation alterations. Pimobendan administration was associated with a significant increase in heart rate, cardiac index and decrease in systemic vascular resistance index. A significant increase in proportion of perfused vessels for all vessels (+8%, [2; 14], P  = 0.01) and small vessels (+8% [1; 14], P  = 0.03), in microvascular flow index (+0.31 AU, [0.04; 0, 58], P  = 0.03) were noticed, as well as a decrease in heterogeneity index (−0.34 [−0.66; −0.03], P  = 0.04) and De Backer score for all vessels (−1.04, [−1.82; −0.25], P  = 0.02). In conclusion, in a simple model of pharmacologically induced hypotension, pimobendan was associated with an improvement in several microcirculatory parameters. Highlights: We explored the microcirculatory and macrocirculatory effects of pimobendan. Pimobendan was associated with sublingual microcirculation improvement. Pimobendan was associated with an increase in cardiac output. Pimobendan induced a decrease in systemic vascular resistance.